2001
DOI: 10.1002/1521-4184(200110)334:10<305::aid-ardp305>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antifungal activity of 3,3'-ethylenebis(5-alkyl-1,3,5-thiadiazine-2-thiones)

Abstract: In a search for promising antifungal compounds, nine new 3,3'‐ethylenebis(5‐alkyl‐1,3,5‐thiadiazine‐2‐thiones) were synthesized by the reaction of ethylene diamine, carbon disulfide, formaldehyde, and the appropriate alkyl amine. The title compounds were tested for their antifungal activity in vitro against pathogenic (Trichophyton rubrum and Candida albicans), phytopathogenic (Penicillum expansum, Trichoderma hazianum, and Fasarium oxysporum), and aflatoxin producing (Aspergillus flavus) fungi. These compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Antifungal compounds with a 1,3,5-thiadiazine core Compounds containing a 1,3,5-thiadiazine core have been demonstrated to possess antifungal properties. It has become well established that the 1,3,5-thiadiazine-2-thione moiety exhibits antifungal activity through the production of isothiocyanate and dithiocarbamic acids [69][70][71][72][73][74][75][76][77][78] In 2001, Hussein et al [79] reported on several new derivatives of the 1,3,5-thiadiazine-2-thione core. The study was based on introduction of two moieties of 1,3,5-thiadiazine-2-thione through an ethylene bridge and investigation of the antifungal activity of these structural analogues.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antifungal compounds with a 1,3,5-thiadiazine core Compounds containing a 1,3,5-thiadiazine core have been demonstrated to possess antifungal properties. It has become well established that the 1,3,5-thiadiazine-2-thione moiety exhibits antifungal activity through the production of isothiocyanate and dithiocarbamic acids [69][70][71][72][73][74][75][76][77][78] In 2001, Hussein et al [79] reported on several new derivatives of the 1,3,5-thiadiazine-2-thione core. The study was based on introduction of two moieties of 1,3,5-thiadiazine-2-thione through an ethylene bridge and investigation of the antifungal activity of these structural analogues.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
“…Synthesis of 3-3 0 -ethylenebis(5-alkyl-1,3,5-thiadiazine-2-thiones) (Compounds 69a-i). The data included in this scheme are taken from [79]. 100 28 22 12 -19 16 50 -19 16 --10 25 --14 ---69b 100 --10 7 13 7 50 --10 --7 25 -----9 compounds not only showed no inhibitory effects on growth or sporulation of the tested fungal species, but also appeared to give rise to a dense mycelial growth.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocyclic compounds containing thiones have shown a wide range of pharmacological activities, such as antimicrobial [1][2][3][4], antidepressant [5], antitubercular [6], antihistamines [7], anti-HIV [8], and others [9][10][11][12]. Pyrimidine rings, on the other hand, are important substructures in natural products like nucleic acids and vitamin B1 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some lipid derivatives of INH were synthesized, but their amphiphilicity and self-assembling property were not investigated [9,11]. The derivatives from tetrahydro-2H-1,3,5-thiadiazine-2-thione (THTT) attracted attention because of their potential antimicrobial activity [12][13][14][15], and especially anti-tubercular activity [16]. In this study, we exploited the monolayers of five synthesized lipid derivatives of INH at the air/water interface and revealed the rule of molecular self-assembly in water.…”
Section: Introductionmentioning
confidence: 99%